If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24-3h=6
We move all terms to the left:
24-3h-(6)=0
We add all the numbers together, and all the variables
-3h+18=0
We move all terms containing h to the left, all other terms to the right
-3h=-18
h=-18/-3
h=+6
| y-45=23y+121 | | 6x-3=5x-17 | | k-9=2k | | 9t-32=58 | | 14+13y=20y-21* | | X(-7x+4)-3x=93 | | 7/2x+1/2x=22*1/2+9/2x | | 3p-21=54 | | 1=-5+p/4 | | -15b+21+5b=-19* | | 2/3(6x+5)=5/9 | | 3(x-4)=2(-2x+1)* | | 8y-25=7y+10 | | x+90=6x-5 | | -q+35=57 | | 67 =3x−7 | | 7/2x+1/2x=(22)1/2+9/2x | | 6=m÷3 | | 10n-5=75 | | 2x=63/5=19 | | 3(x-2)+4x=2(x+2)+5 | | 20+h=800 | | h+11.2=−11.2 | | 1=22-3p | | 8a-4-5a-2=12a | | (2x-4)=42 | | 2x+.99=x+1.98 | | 13=4x+657 | | (Y-4)^2=2y^2-15y+22 | | 5/x=27/4 | | 10-2xx=-2 | | 4x-5=8x+20 |